Properties and microstructure of composite cement paste with diatomaceous earth powder (DEP) from Aceh Besar district – Indonesia - Hasan, Muttaqin; Saidi, Taufiq; Husaini, H (Asia-Pacific Journal of Science and Technology, 2021)
The research was conducted to determine the properties of composite cement paste prepared using diatomaceous earth powder (DEP) from Aceh Besar District, Sumatra Island, Indonesia. The focus of this study was on characteristics such as water demand, setting time, flow, compressive strength, and microstructure. The process involved calcining the diatomaceous earth at a temperature of 600 oC for 4 h, ground, and sieved with #200 to produce a powdered form. The DEP was blended with Ordinary Portland Cement (OPC) to produce a composite cement with DEP content of 0%, 10%, 20%, and 30% (w/w). The DEP, OPC, and water were mixed to produce a paste while the procedures for the test were in line with EN and ASTM Standards. Furthermore, the fresh paste was tested for the water required for normal consistency, setting time and flow while the compression for the 50 mm size cube specimens was determined at the ages of 28 and 120 days. The analysis of the microstructure at the age of 120 days was evaluated using the scanning electron microscopy (SEM) image. The water demand was found to have increased with the DEP content but the initial setting time and flow decreased. It was also discovered that 10% and 20% DEP in composite cement had almost the same compressive strength as OPC paste. Moreover, the SEM image showed the presence of Ca(OH)2 in OPC paste while a massive structure of calcium silicate hydrate (CSH) was observed in the composite cement pastes with 10% and 20% DEP.